2019
DOI: 10.1002/ana.25417
|View full text |Cite
|
Sign up to set email alerts
|

Motor behavior unmasks residual cognition in disorders of consciousness

Abstract: Disorders of consciousness (DOC) are a common consequence of severe brain injuries, and clinical evaluation is critical to provide a correct diagnosis and prognosis. The revised Motor Behavior Tool (MBT-r) is a clinical complementary tool aiming to identify subtle motor behaviors that might reflect residual cognition in DOC. In this prospective study including 30 DOC patients in the early stage after brain injury, we show that the revised MBT-r has an excellent inter-rater agreement and has the ability to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 14 publications
4
41
0
Order By: Relevance
“…Indeed, the data showed similar patterns of rapid and good functional and cognitive evolution in both groups. Altogether, these observations suggest the high potential for recovery of CMD patients and are aligned with clinical and paraclinical expectations that the presence of residual cognition/ covert awareness may lead to a more favorable outcome [10,[27][28][29][30]. Residual cognition indicates preserved high-processing integration [27,31] suggesting that CMD individuals may present a higher level of connected brain networks than those with DOC.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Indeed, the data showed similar patterns of rapid and good functional and cognitive evolution in both groups. Altogether, these observations suggest the high potential for recovery of CMD patients and are aligned with clinical and paraclinical expectations that the presence of residual cognition/ covert awareness may lead to a more favorable outcome [10,[27][28][29][30]. Residual cognition indicates preserved high-processing integration [27,31] suggesting that CMD individuals may present a higher level of connected brain networks than those with DOC.…”
Section: Discussionsupporting
confidence: 73%
“…Just before admission to the acute neurorehabilitation unit, or on entry, the assessment was complemented with the MBT or MBT-r, according to the routine clinical diagnosis guidelines developed by the acute neurorehabilitation unit for the admission procedure. MBT/MBT-r uses an easy dichotomous scoring method to identify signs of residual cognition/conscious awareness as previously described in details [10]. Based on CRS-R and MBT/MBT-r, we therefore categorized patients as either suffering real alteration of consciousness (i.e., DOC, ranging from coma to UWS and MCS) or as presenting with potential clinical CMD (i.e., patients whose conscious awareness is preserved according to MBT/MBT-r yet not clinically identified using the CRS-R due to severe motor defects).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Good practice recommendation: Despite the absence of eligible studies, spontaneous motor behavior and automatic motor responses may be observed and documented in the patient charts, including tube pulling, nose scratching, grabbing sheets, leg crossing and localizing behavior, as these may reflect a higher level of residual consciousness ( very low evidence, weak recommendation ). Indeed, some spontaneous behaviors have been suggested as indicating cortically mediated abilities such as automatic motor responses (which is included in the CRS‐R ) or psychomotor agitation .…”
Section: Resultsmentioning
confidence: 99%
“…The qualification process of patients presenting disorders of consciousness (DOC) is still under development, and therefore, a number of diagnostic methods analyzing pathomechanism, clinical evaluation, and outcome predictions is required for accurate diagnosis [108]. Despite the approved classification of DOC, the latest studies indicate the necessity for inclusion of a new category of patients with cognitive and motor dissociation (CMD) [109,110].…”
Section: Discussionmentioning
confidence: 99%